Between the Sustainable Development Narrative and the Environmental Crisis: Analysis of School Textbooks in Indonesia - Ganes Gunansyah (Universitas Airlangga, 2022)
This study aims to find out what narratives of sustainable development are dominant and what is limited to the presentation of the contents of elementary school textbooks in Indonesia. This study uses quantitative and descriptive content analysis with an instrument in an analysis sheet based on theory. The data sources are 51 elementary thematic textbooks from grades one to six. The study results show that the concept of sustainable development (SDGs) consists of 17 goals and education for sustainable development (ESD). These aspects include social, environmental, economic Sustainability, inclusive development, generally widely spread across all grade levels with varying portions in each grade. The distribution of material related to Social Sustainability (SS) and Environmental Sustainability (EnS) aspects is presented in a small and limited percentage. Meanwhile, materials about aspects of Economic Sustainability (ES) and Sustainability of Inclusive Development (SID) have the most significant portion. Materials on economic growth and activities and the use of natural resources as the mainstay of sustainable development are still dominant, while the roots of the environmental crisis and prevention of ecological damage are still missing. Keywords: Sustainable Development Goals, Education for Sustainable Development, Textbooks, Environmental Crisis